2005
DOI: 10.1007/s00404-005-0029-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone loss in young women with premature ovarian failure

Abstract: Our study shows that premature ovarian failure has significantly lower levels of bone mineral density than the control group of normal women. We suggest that hormone replacement therapy should be substituted early and consistently in affected patients. Our data also raise questions about whether preservation of bone mass in these patients will require replacement of additional gonadal steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 5 publications
2
37
1
2
Order By: Relevance
“…In the present study, 68% of the POI group had low bone mass, after a median of 4 years of amenorrhea. These data agree with the results of studies reporting that early menopause, whether natural or surgical, is an established risk factor for osteoporosis (9,14,(17)(18)(19). The prevalence of osteoporosis increases markedly after the age of menopause, and the concept that estrogen deficiency is critical to the pathogenesis of osteoporosis was initially based on the fact that postmenopausal women, whose estrogen levels naturally decline, are at highest risk to develop the disease (20).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the present study, 68% of the POI group had low bone mass, after a median of 4 years of amenorrhea. These data agree with the results of studies reporting that early menopause, whether natural or surgical, is an established risk factor for osteoporosis (9,14,(17)(18)(19). The prevalence of osteoporosis increases markedly after the age of menopause, and the concept that estrogen deficiency is critical to the pathogenesis of osteoporosis was initially based on the fact that postmenopausal women, whose estrogen levels naturally decline, are at highest risk to develop the disease (20).…”
Section: Discussionsupporting
confidence: 87%
“…Although the risk of osteoporosis in patients with POI is a source of concern, few studies have compared POI women with two simultaneous reference groups. Uygur et al (9) reported lower BMD in POI patients than in a control group of normal women of similar age. Hadjidakis et al (14) compared bone mass in four groups: early menopause, surgical menopause and two natural menopause groups.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the impaired endothelial function found in women with POI, precursor of more severe vascular abnormalities, was improved by hormonal replacement, further supporting the role of steroids in normal cardiovascular function (Kalantaridou et al, 2004). POI patients present with low BMD, which seems to be greatly influenced by the accelerated bone loss during the first 4-5 years of menopause (Amarante et al, 2011;Anasti et al, 1998;Gallagher, 2007;Uygur et al, 2005;van Der Voort et al, 2003), and hence having an increased risk of fractures compared to their peers who underwent a physiological menopause. Finally, an increased risk for cognitive impairment, dementia and Parkinson disease, inversely proportional with age at menopause, was reported in premature menopausal women following oophorectomy (Rocca et al, 2007(Rocca et al, , 2008.…”
Section: Menopause Principal Consequencesmentioning
confidence: 95%
“…Skeletal health is intimately related to and influenced by gonadal function (10,11). Bone mineral density (BMD) and bone metabolism or turnover have been shown to be independent predictors of risk for fracture (12)(13)(14).…”
mentioning
confidence: 99%